Анализ методов определения политропного КПД центробежного нагнетателя - Олейник, Юрий Анатольевич; Сапрыкин, Сергей Алексеевич; Науменко, Светлана Петровна (НТУ "ХПИ", 2018)
Проанализированы математические модели определения политропного коэффициента полезного действия (КПД) центробежного нагнетателя (ЦБН). Описаны четыре метода определения политропного КПД ЦБН и проведены практические расчеты политропного КПД и коэффициента адиабаты по всем методам. Определен самый простой и точный метод определения политропного КПД ЦБН. Значения коэффициентов адиабаты можно использовать при определении политропного КПД ЦБН после определения коэффициента политропы ЦБН.

Mathematical models used for the determination of the parameters of natural gas and centrifugal supercharger (CSC) were analyzed. Based on these models we can compute the polytropic coefficient of efficiency of the CSC using natural gas parameters for the input and output of centrifugal supercharger. Three mathematical models were taken from the standards for the computation of CSC parameters and one mathematical model was taken from the scientific literature. Based on the above mathematical models we described the four methods of computation of the polytropic coefficient of efficiency of the CSC. The values were suggested for the methods that allow for the accurate computation of the polytropic coefficient of efficiency of the CSC and the coefficient of adiabatic curve of the natural gas. The most accurate method of determination of the polytropic coefficient of efficiency of the CSC has been given. The most accurate method is the easiest method for the computations and it is convenient for the computation of an average value of the coefficient of adiabatic curve of the CSC in-operation. The methods allow us to determine an average value of the coefficient of adiabatic curve of the natural gas and using it in combination with the coefficient of polytrope of natural gas we can easily determine the polytropic coefficient of efficiency of the CSC.
Analyzing the methods of computation of the polytropic coefficient of efficiency of the centrifugal supercharger
Keywords: модель математическая; коэффициент адиабаты; КПД; mathematical model; coefficient of adiabatic